Intermediate microeconomics - Hoag, John H. (World Scientific Publishing Company, 2013)
An intermediate-level textbook introducing core microeconomic theories of consumer and firm behavior, market equilibrium, and efficiency, illustrated with real-world examples and exercises for economics and business students.